2014
DOI: 10.1093/trstmh/tru164
|View full text |Cite
|
Sign up to set email alerts
|

Helminth prevalence among adults in rural Kenya: a stool survey for soil-transmitted helminths and schistosomiasis in Nyanza province

Abstract: Adult STH prevalence was lower than previous studies of children from the same village. Adults with the identified risk factors had a prevalence of ≥20%, which may warrant periodic, targeted deworming of adults with these risk factors given the low cost and low toxicity of anthelmintic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
2
5
3
2
Order By: Relevance
“…This result is in agreement with studies carried out in China, Arba Minch, and previous study conducted in Gondar [ 14 , 18 , 22 ]. In contrast to this finding, previous studies carried out in Kenya and China indicated that females were at higher risk of having IPIs than males [ 19 , 23 ]. This variation of exposure among the different sex groups might be due to difference in occupational exposure in different communities.…”
Section: Discussioncontrasting
confidence: 86%
“…This result is in agreement with studies carried out in China, Arba Minch, and previous study conducted in Gondar [ 14 , 18 , 22 ]. In contrast to this finding, previous studies carried out in Kenya and China indicated that females were at higher risk of having IPIs than males [ 19 , 23 ]. This variation of exposure among the different sex groups might be due to difference in occupational exposure in different communities.…”
Section: Discussioncontrasting
confidence: 86%
“…Xin et al from China reported that females are 2.05 times (95% CI = 1.01–4.17) more likely to acquire intestinal parasite infections than males [23]. Females were also at higher risk according to findings in Kenya by Anderek et al [22]. Age and sex were not significantly associated with intestinal helminth infection in this study.…”
Section: Discussionmentioning
confidence: 37%
“…Hook worms were the most frequent helminths in China and Northwest Ethiopia with rates of 4.3% and 11.1% respectively [11, 13]. A stool survey from adult outpatient attendants in Kenya also revealed highest prevalence of hook worms (13.1%) among intestinal helminthes [22]. Variation in the relative distribution of helminth species based on environmental factors might be a reason for such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain conditions, these fertilized eggs can live in the environment for several months. Infection occurs through accidental ingestion of eggs or penetration through the skin [16].…”
Section: Fecal-oral Route: Highway For Pathogensmentioning
confidence: 99%